Expressions of HPV 16-E6 in Esophageal Carcinoma and its Clinical Significance - Xing Zhao; Rajina Sahi; Yu-Yang Zhao; Ju Wang; Chun-Hui Li (Journal of College of Medical Sciences-Nepal, 2015)
Background and Objective: The role of (Human Papilloma Virus) HPV in cancer of certain anatomical location, such as cervix, has been widely recognized. The present study was conducted to explore the association between HPV 16-E6 protein and esophageal squamous cell carcinoma. Methods: SP immunohistochemical method was used to examine the expression of HPV 16-E6 in 50 cases of esophageal squamous cell carcinoma, 10 cases of normal esophageal squamous cell and 10 cases of adjacent tissue. Results: The expression of HPV 16-E6 was significantly higher in esophageal carcinoma than in normal esophageal mucosa and in adjacent tissue. The expressions of HPV 16-E6 had significant correlation with invasive depth (P<0.05), but not with patient age, lymph node metastasis, tumor size (P>0.05). Conclusion: HPV 16-E6 can promote the growth and metastasis of esophageal squamous cell carcinoma and can be a prognostic factor of esophageal squamous cell carcinoma. DOI: http://dx.doi.org/10.3126/jcmsn.v10i4.12970 JCMS Nepal 2014; 10(4):1-5